2008
DOI: 10.1142/s0218301308010039
|View full text |Cite
|
Sign up to set email alerts
|

Study of Alpha Decay of Super Heavy Elements Using S-Matrix and WKB Methods

Abstract: A comparative study of the S-matrix and the WKB methods for the calculation of the half widths of alpha decay of super heavy elements is presented. The extent of the reliability of the WKB methods is demonstrated through simple illustrative examples. Detailed calculations have been carried out using the microscopic alpha-daughter potentials generated in the framework of the double-folding model using densities obtained in the relativistic mean field theories. We consider alpha-nucleus systems appearing in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…(28) with energy E at the above-barrier energies for the potential given by eq. (15). The potential parameters are V0 = 8, a = 3, b = 3.5.…”
Section: Resonance Position Resonance Positionmentioning
confidence: 99%
See 3 more Smart Citations
“…(28) with energy E at the above-barrier energies for the potential given by eq. (15). The potential parameters are V0 = 8, a = 3, b = 3.5.…”
Section: Resonance Position Resonance Positionmentioning
confidence: 99%
“…Evaluations of such states are very important in areas like nuclear scattering and decay of unstable nuclei via alpha decay, proton emission etc. as evident from refs [14][15][16][17][18][19]. A detailed procedure exists for the study of such states in 3D scattering theory.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Thirdly, exact expression for transmission coefficient through the barrier has been used to calculate the half-lives whereas in the earlier studies transmission probabilities through the barrier have been calculated using WKB approximation method. In a recent study, it has been shown that the transmission probabilities calculated using WKB method are insensitive to the tail region of the barrier potential especially for large half-life values [10]. In order to test the accuracy of WKB method we have calculated T WKB and T Exact for Eckart barrier of different ranges.…”
Section: Discussionmentioning
confidence: 99%